Bacteria-invertebrate interactions as an asset in developing new antifouling coatings for man-made aquatic surfaces. (15th February 2021) - Agostini, Vanessa Ochi; Muxagata, Erik; Pinho, Grasiela Lopes Leães; Pessi, Igor Stelmach; Macedo, Alexandre José
Abstract: Economic losses can result from biofouling establishment on man-made structures. Macrofouling causes damage to artificial substrates, which justifies the need for its control. However, the antifouling coatings employed nowadays are typically not safe for the environment. Microfouling can affect macrofouling colonization, and thus represents a potential target for alternative antifouling control. From both ecological and economical points of view, information on the ecology and interactions between micro- and macrofouling are crucial to develop successful and safe control strategies, which will prevent biofouling development on man-made structures while preserving water quality and the safety of non-target organisms. This study presents a metabarcoding analysis of biofilm-associated marine bacteria (16S-rRNA-gene) and fungi (ITS-region), with the aim to understand invertebrate settlement over time on hard substrates exposed to natural condition ( Control ) and two treatments ( Antimicrobials and Antifouling Painted ). Biofouling composition changed with exposure time (up to 12 days) and showed differences among Control and Antimicrobials and Painted treatments. Antimicrobial treatment influenced more the biofouling composition than traditional antifouling paint (Cu2 O-based). Both treatments caused microbial resistance. Macrofouling establishment was strongly influenced by Gram-negative heterotrophic bacteria (mostly Proteobacteria and Bacteroidetes). Nevertheless, each macrofouling taxon settled in response to a specific biofilm bacterial composition, although other factors can also affect the biofouling community as the condition of the substrate. We suggest that proper friendly antifouling technologies should be focused on inhibiting bacterial biofilm adhesion. Graphical abstract: Image 1 Highlights: The study was designed to understand relationships between micro- and macrofouling. Metabarcoding detected microbial biofilm-associated on surfaces in sea water samples. Invertebrate settlement assessed under natural, antimicrobial and antifouling paint treatments. Macrofouling settlement is dependent on the composition of the bacterial biofilm. Each macrofouling taxon responds to a specific bacterial composition.